A case study of sustainable livelihood strategy of women porters at Entikong-Tebedu - Khalil Ur Rahman, Isma Rosila Binti Ismail, Parveen Kaur, Nurul Nadzatul Farah Binti Mohd Khairi,; Jawaid, Arif (Opción, 2019)
This article reveals the case study of women porters (tukang pikul) at the Entikong-Tebedu border by taking the sustainable livelihood framework. A qualitative approach formed the structure of enquiry adopted. Qualitative research is an interdisciplinary field involving an interpretative, naturalistic approach to its subject matter. As a result, the women porters were mostly motivated by the desire to support their household, in fulfilling basic daily expenses. In conclusion, this informal activity is an important source of income for the women thus, with the right livelihood strategies their livelihood outcome would remain sustainable.